The Impact of Applying the Principles of Good Governance on the Strategic Performance of Operations in Family Businesses: An Applied Study on A Sample of Family Businesses Operating in the Egyptian Market - Tawfik, Mabrouk Attia Mabrouk (The Arab Journal of Administration, 2024)
The issue of good governance or good management has received great attention recently in many companies and institutions, and family businesses represent a model for the oldest and most common of these institutions in the world and in many countries. Family businesses represent more than 70% of all companies in different countries, where they play Family businesses range from small and medium-sized companies to large conglomerates that operate in multiple fields and countries, and then these companies seek to adopt modern management practices and methods such as good governance and management to improve and develop the strategic performance of their operations. Hence, the aim of this research is to identify the relationship between the application of the principles of good governance and the development of the strategic performance of operations in family companies operating in the Egyptian market, through the application on a sample of 430 family businesses in the Greater Cairo Region (Cairo, Giza and Qalyubia governorates). Through the descriptive analytical approach and by using the survey as a tool for collecting the necessary data for the study and analyzing this data through the statistical software package used in the social sciences SPSS. The study found a statistically significant relationship between the application of the principles of good governance and the development of the strategic performance of operations (competitive performance of operations - operational performance of operations - financial performance of operations) in family companies operating under study and research. The study recommended the companies under study and research through the Action Plan entry to the need to adopt the concepts of good governance in order to develop the strategic performance of their operations and the need to pay attention to strategic planning processes and to select efficient boards of directors that seek to develop the performance of operations in the long run.